2015
DOI: 10.1002/2014wr015773
|View full text |Cite
|
Sign up to set email alerts
|

Water storage changes as a marker for base flow generation processes in a tropical humid basement catchment (Benin): Insights from hybrid gravimetry

Abstract: In basement catchments of subhumid West Africa, base flow is the main component of annual streamflow. However, the important heterogeneity of lithology hinders the understanding of base flow generation processes. Since these processes are linked with water storage changes (WSCs) across the catchment, we propose the use of hybrid gravity data in addition to neutron probe-derived water content and water levels to monitor spatiotemporal WSC of a typical crystalline basement headwater catchment (16 ha) in Benin. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 119 publications
(240 reference statements)
2
30
0
Order By: Relevance
“…As shown by Hector et al . [] and Séguis et al . [], river flows over recent years in this area mainly originate from perched, seasonal water tables and the contribution of deep (10–20 m) groundwater is negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Hector et al . [] and Séguis et al . [], river flows over recent years in this area mainly originate from perched, seasonal water tables and the contribution of deep (10–20 m) groundwater is negligible.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite drastic deforestation since in Benin 1973 (from 70% to 25% of the total surface), the upper Oueme river discharge (a 15,000 km 2 catchment in which the Donga catchment is embedded) has not shown any great change [Lelay and Galle, 2005;Peugeot et al, 2011]. As shown by Hector et al [2015] and Séguis et al…”
Section: Implication For Land Surface Feedbacks and Water Balancementioning
confidence: 99%
“…Nowadays, gravimetric techniques allow us to monitor hydrogeological effects at a scale of up to 1 km 2 , for signal ranging a few thousands of nm/s 2 to less than 1 nm/s 2 . Several studies have demonstrated the strength of gravity observations for monitoring quantities related to the water cycle, such as soil moisture, rainfall, groundwater storage, hydrothermalism, or snow covering (Creutzfeldt et al, ; Hector et al, ; Hemmings et al, ; Imanishi et al, ; Jacob et al, ; Pool & Eychaner, ; Van Camp et al, ; Wilson et al, ).…”
Section: Monitoring Geophysical Phenomenamentioning
confidence: 99%
“…Ground‐based gravimetry can determine the change of gravity related to Earth rotation fluctuations, to celestial body and Earth attractions, to the mass variations in the direct vicinity of the instruments, and also to distant sources, and to displacement of the instrument itself due to ground deformation. Gravity measurements contribute to risk assessment and mitigation, by improving our understanding of past and present ice mass changes (Kazama et al, ; Lambert et al, ; Larson & van Dam, ; Mazzotti et al, ; Mémin et al, ; Omang & Kierulf, ; Ophaug et al, ; van Dam et al, ), subsidence of low‐lying areas (Van Camp et al, ; Zerbini et al, ), ground water resources (Creutzfeldt et al, ; Fores et al, ; Hector et al, ; Imanishi et al, ; Jacob et al, ; Kennedy et al, ; Lampitelli & Francis, ; Van Camp, de Viron, Pajot‐Métivier, et al, ; Van Camp et al, ), and earthquakes (Imanishi, ; Montagner et al, ; Van Camp et al, ). Concurrently, terrestrial gravity measurements play a key role in the new definition of the kilogram (Stock, ), and our understanding of environmental effects affecting the gravity measurements will be useful to assess the Newtonian noise affecting gravitational wave detectors (Coughlin et al, ; Harms & Venkateswara, ).…”
Section: Introductionmentioning
confidence: 99%
“…For reducing tides, Tanaka et al (), for instance, used the Baytap program (Tamura et al, ); other studies preferred ETERNA (Wenzel, ), for example, in Meurers et al (), or VAV program (Venedikov et al, ), for example, in Arnoso et al (). Much of the same variety can be found even in studies focusing on identical or similar phenomena, like local water storage changes, where for the correction of global atmospheric gravity effects; some studies (Hector et al, ) chose the École et Observatoire des Sciences de la Terre (EOST) atmospheric loading (Boy & Hinderer, ); and others (Creutzfeldt et al, ) preferred Atmacs (Klügel & Wziontek, ). Similar examples can by found for continental hydrology and nontidal ocean loading (e.g., Hector et al, ; Mikolaj et al, ).…”
Section: Introductionmentioning
confidence: 99%